The Impact of EU Funds on the Tuorist Attractiveness of a Region - a Case Study - Panfiluk, Eugenia (Studia Oeconomica Posnaniensia, 2017)
This article aims to analyse the impact of the investments co-financed by the ERDF, spent on the development of the tourism sector, using the Gunn model of tourist attractiveness. A theoretical model for assessing the impact of the investments, co-financed by the ERDF, on the tourist attractiveness of a region was developed and subjected to empirical verification. The material for empirical research was collected with the use of a questionnaire. The study involved tourists visiting the Podlaskie voivodeship. The final conclusions allowed the generalization that the developed model for assessing the impact of investments co-financed by the ERDF on the tourist attractiveness of a region can be used to assess the effectiveness of the ERDF management at the regional level, is used for the identification of the strengths and weaknesses of the tourism control system at the regional level towards creating a more attractive tourist area, is used for the determination of the causes of deviations and the evaluation of developmental directions of regional policy plans, and programmes in the area of tourism development, may be used in the planning process of tourism development of a region at the stage of evaluation, as well as further programming, implementation or introduction of changes in relation to the development of a tourist destination.